Assessment of Overall Tourists Experience in Selected Tourism Development Clusters in Northern Philippines - Areola, PhD HSG, Eunice Mareth Querol; Trinidad, Fernando; Flores, Julius (Journal of Sustainable Community Development (JSCD), 2023)
The study aimed to assess the overall tourists' experience in the selected tourism development clusters in Northern Philippines. The design was descriptive, using the quantitative approach on 200 respondents. The findings of the study were: majority of the respondents were aged between 18 and 27 years old, female, single, employed as staff for 0-5 years, participated in educational tour, and the purpose of travel is to learn; the overall experience of the respondents are enhanced by the theme at TDS and TSs in NP-6, harmony of positive cues, elimination of negative cues, mix memorabilia, and the engagement of all their five senses; there is no significant difference in the overall experience of the respondents based on the five principles of experience design based on Pine and Gilmore (1998); the overall experience by the respondents towards TDS and TSs in NP-6 have entertainment, education, escapism, and aesthetic (Pine and Gilmore 1998) in various levels, because the respondent have not reached the richest experiences that encompasses all aspects of all the four realms of experience that form the “sweet spot” around the area where the spectra meet, It concludes that the overall tourists experience in the selected TDS and TSs in NP-6 are enhanced by the theme, harmony of positive cues, elimination of negative cues, mix memorabilia, and the engagement of all their five senses; however, it has not reached the richest experiences that encompasses all aspects of entertainment, education, escapism, and aesthetic. As such, the study recommends the following: 1. DOT, LGUs, and the tourism stakeholders that covers the TDs and TSs in NP-6 should form an inter-agency group that should regularly evaluate the destination development strategy aimed at supporting the development of tourism destinations and enhancing the overall tourists’ experience; 2) The inter-agency group main task is to monitor changes in tourist behavior in the market and guide the tourism stakeholders in the development of its products that would meet the current needs of the tourists; and 3) 3. LGUs at TDs and TSs in NP-6 should regularly conduct inspection of the tourism stakeholders to ensure compliance of the destination development strategy and that the tourists have a positive experience.